Analysis of Fitness Facilities And Effective Use of Crossing Road - Juniardi JUNIARDI; Edi Haryanto (International Conference on Engineering and Technology Development (ICETD), 2013)
Pedestrians are part of the transportation system is no less important than other modes of transportation. Although the act of walking legs look very simple, but it plays an important role in the transport system, because if the impaired pedestrians will affect other parts of the transportation system.Objective analysis of the pedestrians along the road Kartini is to determine the characteristics of pedestrians; seek equality relationship between walking speed, as well as determine the appropriate crossing facilities with pedestrian characteristics.This study analyzes the suitability and effectiveness of the use of level crossings in terms of facilities: traffic volume (V), Volume waders (P), Degree of Saturation (DS), the average traffic Speed, Time Headway, the pass percentage of pedestrian crossing facilities, the comparison between the speed of the vehicle with pedestrian volumes and pedestrian behavior analysis.The suitability of the facility Kartini street crossings diruas calculated based PV2, DS, average Speed, Time Headwaysehingga obtained values: P = 78 people / hour, SD = 0.60, mean velocity = 40.3488 km / h, and a small headwaykendaraan time (LV) vehicles and motorcycles (MC) has a value of time headway of <2.5 seconds which describes the condition of high density, so that at the study site at the Kartini Bandar Lampung according to the requirements and are pelican crossings in accordance with the protector. Of regression and correlation analysis shows the location of Bandar Lampung Kartini road traffic volume did not affect the percentage of pedestrian road as seen from R2 = 0.002, which means the relationship between the volume of pedestrian traffic with only 0.2% indicating a relationship classified as very low. Pelican crossing facilities with protective shield recommended to use the island has given the signal light Kartini Bandar Lampung is a one way street with four lanes.